Implementasi Sistem Informasi Akademik (SIAKAD) dalam Meningkatkan Efisiensi Administrasi Pendidikan di Madrasah Aliyah Negeri - Hendra Kurniawan; Nazla Sofi Adinda; Dea Nadhira Mulyadi; Suci Nurhayati (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
This study aims to examine the implementation of the Academic Information System SIAKAD in improving the efficiency of educational administration at Madrasah Aliyah Negeri. The research method used is descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results show that SIAKAD significantly contributes to accelerating academic administrative processes such as student data management, grade entry, attendance management, and academic report preparation. This system reduces reliance on manual processes prone to errors and speeds up the completion time of administrative tasks. However, several challenges remain, such as limited training for educators and internet network issues affecting system operation. The study concludes that SIAKAD can substantially improve administrative efficiency if supported by adequate training and reliable technological infrastructure. The implementation of SIAKAD also enhances transparency and accountability in academic data management at the madrasah. Therefore, the development and maintenance of this system should be prioritized to support the digitalization of modern and effective educational administration processes.